Improving rowing performance by adjusting oar blade size and angle - van Nieuwburg, W. C. A. M.; van Spreuwel, B. J. J.; Tran, M. T. K.; Yang, M. D.; Greidanus, A.; Mulder, G.; Tummers, M. J.; Westerweel, J.; Suijker, W.; van Wijk, R. (Frontiers in Sports and Active Living, 2023)
A 1:5 scaled rowing boat is used to determine the performance of rowing blades with different sizes and blade angles. This was used to validate the results of a previous study where the optimal blade angle of 15 degrees with respect to the oar shaft was determined (Grift et al., 2021). The input power and speed of the rowing boat can be compared between original and modified oar blades. Measurements in a towing tank demonstrate that a modified rowing blade result in faster rowing by 0.4% at the same input power. Maintaining the same stroke rate, the improvement of the blade efficiency is compensated by using a 4-6% increased blade area to yield the same input power.